2019
DOI: 10.1177/1477153519884097
|View full text |Cite
|
Sign up to set email alerts
|

The effects of illuminance and correlated colour temperature on daytime melatonin levels in undergraduates with sub-syndromal SAD

Abstract: Under the pressure of ensuring student visual performance, this study investigated whether improving the classroom lighting is helpful in relieving the daytime serum melatonin concentration in undergraduates who suffer from sub-syndromal seasonal affective disorder in winter. Two negative control groups (Undergraduates without sub-SAD, lighting conditions 300 lx, 4000K), two positive control groups (undergraduates with sub-seasonal affective disorder, lighting conditions 300 lx, 4000K) and six positive interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Yan et al 27 demonstrated a positive correlation between lighting stimuli (750 lx, 4000 K) from fluorescent lamps and students' learning efficiency and physiological rhythms. Yang et al 28 revealed that increasing the illuminant colour temperature or illuminance during daytime can effectively restrain sub-seasonal affective disorder participants' daytime serum melatonin secretion, which provides suggestions for classroom lighting in sunless areas from the aspect of the melatonin rhythm. The classroom's luminous environment is an important external stimulus regulating circadian rhythms, as well as a crucial factor affecting students' sleep quality, alertness and mood.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al 27 demonstrated a positive correlation between lighting stimuli (750 lx, 4000 K) from fluorescent lamps and students' learning efficiency and physiological rhythms. Yang et al 28 revealed that increasing the illuminant colour temperature or illuminance during daytime can effectively restrain sub-seasonal affective disorder participants' daytime serum melatonin secretion, which provides suggestions for classroom lighting in sunless areas from the aspect of the melatonin rhythm. The classroom's luminous environment is an important external stimulus regulating circadian rhythms, as well as a crucial factor affecting students' sleep quality, alertness and mood.…”
Section: Introductionmentioning
confidence: 99%